2016
DOI: 10.1038/icb.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Human macrophages induce CD4+Foxp3+ regulatory T cells via binding and re‐release of TGF‐β

Abstract: While pro-inflammatory immune responses are a requirement to combat microbes, uncontrolled self-directed inflammatory immune responses are the hallmark of autoimmune diseases. Restoration of immunological tolerance involves both suppression of ongoing tissue-destructive immune responses and re-education of the host immune system. Both functionally immunosuppressive macrophages (M2) and regulatory T cells (Tregs) are implicated in these processes. Their mutual interaction is synergistic in this context and adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 66 publications
4
53
0
Order By: Relevance
“…Multiple studies have reported increased frequencies of Tregs cells in experimental animal studies and in patients treated with MSC . It has furthermore been shown that immunosuppressive macrophages (M2) can induce Tregs cells in vitro . Our results give insight in how MSC driven polarization of monocytic cells may mediate increasing Tregs cell numbers after MSC infusion.…”
Section: Discussionsupporting
confidence: 54%
“…Multiple studies have reported increased frequencies of Tregs cells in experimental animal studies and in patients treated with MSC . It has furthermore been shown that immunosuppressive macrophages (M2) can induce Tregs cells in vitro . Our results give insight in how MSC driven polarization of monocytic cells may mediate increasing Tregs cell numbers after MSC infusion.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, the immunosuppressive function of CD163 + macrophages might be mediated by PD‐L1/L2. Importantly, human macrophages induce FOXP3 + Tregs via binding and rerelease of TGFB, the checkpoint inhibition . Although not statistically significant, a trend of association with SR was found for high CD3 (OR, 3.643), low BTLA (OR, 0.362) and high CD163 (OR, 2.669); results that are also in agreement with the postulated pathogenesis (Table ).…”
Section: Discussionsupporting
confidence: 72%
“…Importantly, human macrophages induce FOXP3 + Tregs via binding and rerelease of TGFB, the checkpoint inhibition. 38 Although not statistically significant, a trend of association with Figure 3 Gene Set Enrichment Analysis (GSEA) of immune markers in active ulcerous colitis, independent series GSE38713, versus normal mucosa. (a) Based on the markers analyzed by immunohistochemistry in this study a protein-protein network analysis was created using STRING.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless these TGF-β + retinoic acid + rapamycin iTregs did not suppress in a, though artificial, xenogeneic in vivo suppression assay (34), highlighting the complexity of assays for determining iTreg suppressive function. A major complication with assays using human iTregs is that these cells lack epigenetic demethylation in the so-called Treg-specific demethylated region (TSDR) in the FOXP3 locus (56, 57) and hence lose FOXP3 upon restimulation (34, 58). Therefore, it would be complicated to study whether GM-CSF + FOXP3 + cells would lose GM-CSF upon restimulation in analogy to the murine system in Ref.…”
Section: Discussionmentioning
confidence: 99%